Age determination and growth of leaping mullet, (Liza saliens R.1810) from the Messolonghi Etoliko lagoon (western Greece) - KATSELIS, G.; KOUTSIKOPOULOS, C.; KASPIRIS, P. (Mediterranean Marine Science, 2002)
This study is the first detailed work on the age and growth of the leaping mullet (Liza saliens, Risso 1810) in the central Mediterranean. During the period 1991-1995 the age and growth of leaping mullet from the Messolonghi -Etoliko lagoon system (western Greek coast) were studied. Age and growth determinations were based upon otolith samples taken from 537 fish. Marginal increment analysis was used to validate age determination. Annulus formation took place around November each year. The back-calculated lengths at age estimated from the otoliths showed no differences between sub-areas of the lagoon system and the recorded limited between-years variability showed no persistent temporal pattern. The maximum age of leaping mullet in the Messolonghi - Etoliko lagoon was 5 years for males and 6 years for females. The von Bertalanffy equation (L‡=32.99±1.25 cm, k=0.258 ±0.017 year-1, t0=-0.47±0.04 year) accurately describes the growth of the total length of leaping grey mullet for all life stages (fry, juveniles and adults). A large spread and length overlap characterized the age groups. The estimated Length-Weight relationships were common for the two sexes (W=0.0079L3.01).